Quo Vadis Protection of The Basic Rights of Indonesian Workers: Highlighting The Omnibus Legislation and Job Creation Law - Nyoman Mas Aryani; Ayu Putu Laksmi Danyathi; Bagus Hermanto (Pandecta Research Law Journal, 2022)
This article focused on the dynamics following the enactment of the Law on Job Creation. Pros and cons were raised publicly, with proponents arguing that the Omnibus Legislation method could be used to propose leaps and further forward steps for national economic acceleration with more effective and efficient investment and the creation of new job fields in Indonesia. However, the opposition argued that this law, enacted using the Omnibus Legislation method, was not prepared and did not involve workers or worker unions in the lawmaking process prior to its enactment. Furthermore, this law has crucial and controversial provisions that weaken workers’ rights fulfillment compared to the previous arrangement. This condition is the primary issue that created a chasm between workers with their rights and their employers, and it is the basis for further analysis of legal norms in the entirety of the Law on Manpower and the Law on Job Creation. With the use of a normative legal research method supported by a statutory law approach and a legal conceptual approach, as well as a legal material searching method and argumentative analysis, legal research is conducted. This article discovers and proposes fundamental principles, concept formulation, and concept proof comprehensively regarding Employment Law policy dynamics in Indonesia and pursues basic rights of workers protection after enactment of the Omnibus Law on Job Creation to ensure the realization of worker rights protection including industrial relations problem, and certainty guarantee that Employer must fulfill.